Reflections:Art Practises in Arctic Art and Design Master´s Program - Huhmarniemi, Maria Eliisa (2018)
The Reflections exhibition presents artworks from the ‘Arctic Art and Design’ Master's programme. Some of the artworks are reflections on the projects that students have done for the programme and some on life in Finnish Lapland. The exhibition artists have come from all over the world to study in Rovaniemi, and some of their studies took place in Northern villages and landscapes. Three of the programme’s teachers are also involved in the exhibition. The exhibition introduces the profile of the ‘Arctic Art and Design’ Master's degree programme.